Abacterial prostatitis of viral etiology and its chronobiological features - V. S. Goydyk; M. V. Novikov; A. I. Gozhenko (Kazimierz Wielki University, 2020)
Urogenital infections are a global health burden all over the world. The combination of general "aging" of the population and improvement of diagnostic capabilities led to a surge in the detection of diseases of the urogenital sphere, much of which have viral etiology. An increase in the load on doctors of the urological profile, especially working at outpatient units, dictates the need to improve the efficiency of their work. The use of mathematical modeling methods in the study of medical records of 600 men with urogenital diseases made it possible to ascertain the seasonality of requests for medical help, as well as to create a prognostic model, the use of which suggests the possible number of referrals for patients with abacterial prostatitis of viral etiology during any month of the next year.